2013
DOI: 10.1111/jce.12325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biomarker‐Based Approach for the Detection of Asymptomatic Brain Injury During Catheter Ablation of Atrial Fibrillation

Abstract: Serial assessment of serum protein S100B may improve detection of asymptomatic acute brain injury in patients undergoing radiofrequency catheter ablation of AF. In our study, the incidence of these events was 1.7% when evaluated only by DW-MRI, but the incidence increased to 5% after employing the more sensitive biomarker-based approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
9
2
3
Order By: Relevance
“…Our method of AF ablation and the catheter setup were described in detail elsewhere [ 9 ]. Using transfemoral approach, a decapolar catheter for the left atrial pacing was inserted in to the coronary sinus, a steerable mapping catheter for the His pacing was introduced to the right ventricle, and a 6-F fluid-filled pigtail catheter for measurement of the LV pressure was advanced antegradelly to the LV cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Our method of AF ablation and the catheter setup were described in detail elsewhere [ 9 ]. Using transfemoral approach, a decapolar catheter for the left atrial pacing was inserted in to the coronary sinus, a steerable mapping catheter for the His pacing was introduced to the right ventricle, and a 6-F fluid-filled pigtail catheter for measurement of the LV pressure was advanced antegradelly to the LV cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Moderní zobrazovací metody přinášejí možnost diagnostikovat i ,,tiché" asymptomatické léze centrálního nervového systému (CNS) [1,2]. Dlouhodobé důsledky těchto asymptomatických postižení nejsou známé [3].…”
Section: úVodunclassified
“…Zvýšení koncentrace proteinu S-100B zjistili u tří pacientů (5 %), jeden pacient s nálezem ve vztahu k postižení CNS na NMR. Nadlimitní hodnoty proteinu S-100B byly zaznamenány u pacientů s perzistentní formou FS, zvětšenou levou síní (LS), delším procedurálním časem, vyšší dávkou ablační energie a nižší kumulativní dávkou heparinu [3].…”
Section: úVodunclassified
“…However, another study suggested that DW-MRI lacks sensitivity, and the authors investigated whether detection of cerebral damage during IPV can be improved by assessing a sensitive biomarker of neuronal injury: protein S100B. 9 The authors found that a higher incidence of silent stroke can be revealed by the biomarker-based (protein S100B) approach than by DW-MRI alone. 9 …”
Section: Introductionmentioning
confidence: 99%